ANALISIS PEMBIAYAAN BSM IMPLAN PNS (Studi Pada Bank Syariah Mandiri Kantor Cabang Pembantu Bogor Sudirman) - Diana Debora; Tubagus Rifqy Thantawi; Ermi Suryani (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2021)
Abstract This research is motivated by the development of BSM Implant financing which is increasing in line with the increasing level of consumption needs of civil servants. BSM Implan PNS Financing is a leading financing product at the moment, where this product is a sharia concept financing using a Murabahah contract that is offered to civil servants who need funds. Good for multipurpose financing, education, and home renovations. In providing BSM financing, KCP Bogor Sudirman has procedures that must be followed by customers, it is necessary to analyze BSM Implant financing, such as how the BSM Implant financing procedure flows, what obstacles are experienced in the BSM Implant financing process and what are the views of Islamic law on Implant financing BSM. This research is qualitative in nature and the data collection method is by conducting interviews. This data collection method was carried out at Bank Syariah Mandiri KCP Bogor Sudirman, the analysis used in this study was descriptive qualitative. The results of the study show that the flow of financing procedures is the first process that must be considered and carried out by the company to determine the initial steps of the financing process, such as what BSM Implant financing requirements must be met by customers. With this financing, it is hoped that good communication will be established between the bank and the customer. In carrying out the BSM Implant financing process, there are several obstacles encountered in the BSM Implant financing implementation process, namely the initiation process, the verification process, the contract/agreement process, and the disbursement process. And according to Islamic law, the implementation of BSM implant financing at Bank Syariah Mandiri KCP Bogor Sudirman is in line with Islamic law. This is corroborated by DSN MUI Fatwa No: 04/DSN-MUI/IV/2000 concerning Murabaha which states that this guarantee is permissible and strengthened by DSN Fatwa No: 44/DSN-MUI/VII/2004 concerning multilingualism.